How to Retain and Motivate Employees in an Organization: A Case Study of an Infrastructural Company - Velamati, Antara (2015)
Employee turnover is one of the biggest challenges that every sector globally is facing today. It is increasingly reaching the attention of managers today as they can see the number of employees quitting their organizations. The cost of an employee leaving an organization is proved to be one of the highest costs for an employer. Therefore the main purpose of this research is to reduce employee turnover by retention strategies and motivation strategies. Retention is that process of keeping employees in the organization for the longest period. With the rise in competition retaining highly valuable employees is a competitive advantage for any organization. As every individual will have different motivations or wants managers are facing the challenge of identifying each employees needs and wants in order to retain them. Therefore the main aim is to try retaining employees through motivation as that is one of the most important factors irrespective of the individual’s needs. Every human requires some kind of motivation in order to perform and to achieve goals. It can be in the form of words such as appreciation or rewards such as gifts or hike in salary. Therefore retention strategies and some motivational theories have been included. This research has been conducted considering the quantitative approach method. A questionnaire was sent out to 100 respondents but received only 84 responses from an Indian Infrastructural Company. The survey questionnaire was designed under four main headings which are retention strategies, motivation strategies, organization culture & turnover strategies. The main objective was to know what factors made employees leave the organization and what factors would retain them for a longer period.